Frontal cortex functional activity modulation impact on the stereotypic, emotional and postural behavior in rats during the interictal period of pilocarpine-induced chronic epileptogenesis - Kashchenko, O.; Stoyanov, O.; Volokhova, G.; Berbek, V.; Voloshchuk, D.; Pryshchepa, O.; Zayats, L.; Tatarko, S. (Journal of Education, Health and Sport, 2023)
The cholinergic mechanisms role determination in epileptogenesis attracts the attention of researchers. Pilocarpine administration in rats contributes to chronic form of epileptiform activity development characterized by the presence of a pronounced acute stage and an interictal period - free from behavioral convulsive reactions. We consider the most important feature of the pilocarpine-induced seizures interictal period might be the change of various forms of nonconvulsive behavior. Attempts to investigate the animals’ behavioral reactions details during the seizure-free interictal period, as well as to determine the mechanisms of similar types of behavior formation, are interesting. The purpose of the work is to investigate the motor, stereotypic and aggressive-defensive behavior of rats throughout the interictal period of pilocarpine-induced convulsive syndrome with a frontal cortex functional activity change. It was found that the severity of non-convulsive behavioral reactions in the interictal period during pilocarpine-induced chronic seizures is mostly determined by the frontal cortex functional state. At the same time, the frontal cortex hyperactivation is an important feature of pilocarpine-induced chronic epileptogenesis. The authors proved that when the frontal cortex is activated in rats, there is an increase in horizontal and vertical motor activity, as well as the expressiveness of emotional reactions in the “open field” test and the strengthening of the aggressive-defensive behavior. In conditions of this part of the cortex selective destruction the opposite behavioral effects are noted which confirms the important role of the frontal cortex in the interictal non-convulsive behavior formation. Observed behavioral effects during the frontal cortex functional activity modulation, according to the authors, indicate the reasonability of regulatory influences searching aiming forward this brain part to activate complex mechanisms aimed to pilocarpine-induced chronic epileptiform activity elimination.